2022
DOI: 10.3389/fphar.2022.1065029
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of DOCK8 in tumorigenesis by regulating immunity and the application of nanotechnology in DOCK8 deficiency therapy

Abstract: The dedicator of cytokinesis 8 (DOCK8) immunodeficiency syndrome is a severe immune disorder and characterized by serum IgE levels elevation, fungal and viral infections, dermatitis and food allergies. It was well known that DOCK8 is crucial for the survival and function of multiple immune related cells. However, the critical role of DOCK8 on tumorigenesis through regulating immunity is poorly investigated. Accumulating evidences indicated that DOCK8 could affect tumorigenesis by regulating the immunity throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Deletion or down-regulation of DOCK8 was detected in leukemia, lung cancer, renal cell carcinoma, low-grade gliomas and childhood hairy cell astrocytoma. It has been shown that DOCK8 promotes the mesenchymal-type movement of hepatocellular carcinoma (HCC) cells, and the expression of DOCK8 is negatively correlated with the occurrence of HCC [25]. In our patient cohort, DOCK8 deletions and duplications were not associated with adverse events according to statistical analysis (Figure 6).…”
Section: Discussionmentioning
confidence: 69%
“…Deletion or down-regulation of DOCK8 was detected in leukemia, lung cancer, renal cell carcinoma, low-grade gliomas and childhood hairy cell astrocytoma. It has been shown that DOCK8 promotes the mesenchymal-type movement of hepatocellular carcinoma (HCC) cells, and the expression of DOCK8 is negatively correlated with the occurrence of HCC [25]. In our patient cohort, DOCK8 deletions and duplications were not associated with adverse events according to statistical analysis (Figure 6).…”
Section: Discussionmentioning
confidence: 69%
“…The dedicator of cytokinesis 8 (DOCK8), a well-studied member of the DOCK protein family, was an atypical guanine nucleotide exchange factor (GEF). DOCK8 has been reported mainly expressed in the immune system, kidney, lung, placenta, pancreas, and microglia of the central nervous system (CNS) (Zhang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Haploidentical HSCT with post-transplant cyclophosphamide has also been shown to have an emerging role in these children [30]. Future studies are focussing on improving outcome with possible nanotechnology in HSCT for these disorders [31].…”
Section: Discussionmentioning
confidence: 99%